Effect of Halal Certification, Halal Awareness, Product Quality and Price on Consumer Purchase Interest (Case Study: Mie Ayam Mushroom Haji Mahmud S.) - Sri Rahmawati Isnaini Ginting; Sugianto Sugianto; Reni Ria Armayani Hasibuan (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the effect of halal certification, halal awareness, product quality and price on consumer buying interest. This research was conducted using quantitative research. The population in this study amounted to 3,000 with a sample of 97. The sampling method was simple random sampling technique. This study uses primary data, with multiple linear regression data analysis method using SPSS 15. Based on the results of the first hypothesis test, it is known that the significant value of halal certification is 0.045 (sig < 0.05) with a t-count value of 2.030 > 1.986 (t-count > t-table). The second hypothesis test shows a significant halal awareness of 0.002 (sig < 0.05) with a t-count value of 3.626 > 1.986 (t-count > t-table), the third hypothesis shows a significant product quality 0.006 (sig < 0.05) with a t-value -count 2.812 > 1.986 (t-count > t-table), the fourth hypothesis is significant 0.910 (sig > 0.05) with t-count value -0.113 < 1.986 (t-count < t-table). Based on the results of the fifth hypothesis test, it is known that the significant value is 0.000 (sig < 0.05) with an f-count value of 32.542 > f-table 2.471. The results of this study indicate that Halal Certification, Halal Awareness, Product Quality and Price simultaneously have a significant effect on consumer buying interest.